Proposal for a visual-semantic web CV (CVSw) - Salmaso, Luisa; Bagnariol, Silvio; Tosato, Paolo (Formazione & insegnamento, 2012)
This article presents the proposal of a device meant for the active construction of one’s own Curriculum Vitae: the representational portrayal in a web environment, called Visual-Semantic web CV (CVSw). The leading hypothesis is that, thanks to its value for guidance and to its enhanced visual features, this apparatus allows for the elicitation of cognitive processes—and thus constitutes a useful medium able to facilitate organizational, communicative, and educational capabilities. This tool includes a progressive stepby-step processing within a virtual environment. When involved in the constructive process, the individuals are led to structure their own life experience according to three areas related to the European CV model: education/training, activities, and products. CVsw introduces two new agents of innovation: the attribution of semantic meanings and values, and userfriendly graphic display meant for both the creator and the final user.